Moraxella catarrhalis bacteraemia and prosthetic valve endocarditis - Shahani, Lokesh (BMJ Case Rep, 2015)
Moraxella catarrhalis, once considered a non-pathogenic coloniser of the oropharynx, has now been recognised as a true pathogen and is reported in cases of bacteraemia. A 63-year-old man with an aortic bioprosthetic valve was brought to the emergency room with altered mental status. Initial blood cultures revealed Gram-negative diplococci on Gram stain; echocardiogram showed a 5 mm vegetation on the aortic bioprosthetic valve. The blood cultures grew M. catarrhalis and the patient was treated medically for prosthetic valve endocarditis with 6 weeks of ceftriaxone and had a favourable clinical outcome. M. catarrhalis has a high prevalence of β-lactamase production and hence the patient was treated with ceftriaxone. This case highlights the importance of considering M. catarrhalis as a pathogen in cases of invasive disease.